A Comparison of Amniotic Fluid Index versus Single Deepest Pocket Method in Terms of Maternal and Perinatal Outcome in Late Term Pregnancies - Fauzia Anbreen, Abeer, Razia Bibi, Reema Fateh, Sadia Hanif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Over diagnosis of isolated oligohydramnios is associated with increased obstetrical intervention without improving maternal and perinatal outcome. Objective of this study is to evaluate two methods of amniotic fluid volume assessment regarding obstetrical intervention frequency and its effect on maternal and perinatal outcome. Materials and Methods: This prospective study was conducted at a Private Hospital of Dera Ismail Khan and Khyber Teaching Hospital, Peshawar from 1st January 2017 till 31st December 2019. All pregnant patients with singleton, un-complicated pregnancy with period of gestation from 41 weeks to 41 weeks 6 days, live fetus were included in the study. Women who met the eligibility criteria were assigned to two different techniques of amniotic fluid assessment, first amniotic fluid index( AFI) method and second single deepest vertical pocket(SDVP) method. Data was recorded on a specially designed proforma. The socio-demographic variables were age in years, parity. Continuous variable was measured on numerical scale and expressed as mean and SD. Research variables were maternal outcome and perinatal outcome in terms of oligohydramnios frequency, induction of labour, caeserean section, fetal distress, NICU admission, A/S < than 7 at 5 minutes. Chi-sq test of significance was applied. Results: A total of 160 patients met the inclusion criteria. In first group 30 (37.5%) and in second group18 (22.5%) had oligohydramnios. In AFI group 10 (33.3%) and in SDVP group 3(16.66%) had caesereans section. Induction of labour was 30(37.5%) in AFI group and 18(22.5%) in SDVP group. These results were statistically significant with a p value less than .05 at 5% significance level. Fetal distress, A/S < than 7 at 5 minutes, NICU admission results were not statistically significant for two groups. Conclusion: SDVP technique gave less abnormal results, less intervention with no significant difference in maternal and perinatal outcome. Keywords: Amniotic fluid, Oligohydramnios, Caesarean section.